Subtropical broad-leaved urban forests as the foremost dynamic and complex habitats for a wide range of bird species - Rajpar, Muhammad Nawaz; Khan, Shahab Ali; Ditta, Allah; M. Ali, Hayssam; Ullah, Sami; Ibrahim, Muhammad; Rajpar, Altaf Hussain; Zakaria, Mohamed; Salem, Mohamed Z. M. (MDPI AG, 2021)
Broad-leaved subtropical forests are the most productive, diversified, and complex ecosystems on the planet. Unfortunately, they are currently under severe threat from anthropogenic activities, such as. deforestation, housing settlements, and agricultural expansion. In response to these severe effects, the present study was conducted to explore the current conservation status and population structure of a wide range of bird species inhabiting different subtropical broad-leaved urban forests of Pakistan. In total, 2879 individuals comprising 53 species and 28 families were detected between December 2017 and November 2018 as revealed through the distance sampling line transect method. The habitat selection among bird species varied according to vegetation structure and composition, food resources, adjoining habitats, and human settlements. According to IUCN Red List data, one species was deemed vulnerable out of 53 bird species, while the remaining 52 species were ranked as ofleast concern. The findings of the density analysis revealed that bird density varied between six subtropical broad-leaved forests. Palamar (3.954 ± 0.221 birds/ha) and Kityari (3.138 ± 0.162 birds/ha) were densely populated, whereas Kamal Khan (1.102 ± 0.178 birds/ha) was of the least concern. Likewise, the diversity analysis showed that Kamal Khan was a more diverse habitat (Shannon–Wiener Index; H’ = 3.581 ± 0.021). Shahabad was richer (Margalef Richness Index; R1 = 8.007 ± 0.053) and Dob Ghar was evenly distributed (Pielou J Evenness Index; E = 0.940 ± 0.005) compared to other urban habitats studied. Eight foraging guilds were identified among the bird species. Insectivores were the most abundant bird species utilizing the urban dwelling habitats. carnivores/piscivores/insectivores utilized Dob Ghar forest, while more frugivores utilized Kamal Khan and Dob Ghar. Based on the data, it was concluded that subtropical broad-leaved urban forests are dynamic, complex, and of vital significance for a diverse range of bird species.